2015
DOI: 10.1364/oe.23.00a371
|View full text |Cite
|
Sign up to set email alerts
|

GaN-based photon-recycling green light-emitting diodes with vertical-conduction structure

Abstract: A p-i-n structure with near-UV(n-UV) emitting InGaN/GaN multiple quantum well(MQW) structure stacked on a green unipolar InGaN/GaN MQW was epitaxially grown at the same sapphire substrate. Photon recycling green light-emitting diodes(LEDs) with vertical-conduction feature on silicon substrates were then fabricated by wafer bonding and laser lift-off techniques. The green InGaN/GaN QWs were pumped with n-UV light to reemit low-energy photons when the LEDs were electrically driven with a forward current. Efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…22,23 However, a further increase in the In content and/or thickness of the UL to enhance the SD trapping frequently has negative impacts on the device performance because it generates threading dislocations (TDs) and absorbs the photons emitted from the MQWs. 24,25 This indicates that the introduction of a UL alone is insufficient to suppress the incorporation of SDs into the MQWs. As a method to further reduce the SDs in n-type GaN other than the introduction of a UL, we have demonstrated the MQWs grown on the surface-etched ntype GaN layer, which showed an improvement in the IQE by a factor of 2.5 in green LEDs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 However, a further increase in the In content and/or thickness of the UL to enhance the SD trapping frequently has negative impacts on the device performance because it generates threading dislocations (TDs) and absorbs the photons emitted from the MQWs. 24,25 This indicates that the introduction of a UL alone is insufficient to suppress the incorporation of SDs into the MQWs. As a method to further reduce the SDs in n-type GaN other than the introduction of a UL, we have demonstrated the MQWs grown on the surface-etched ntype GaN layer, which showed an improvement in the IQE by a factor of 2.5 in green LEDs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several physical mechanisms have been suggested as the origin of the green gap, including the quantum-confined Stark effect, random alloy fluctuation, high dislocation density, and asymmetric carrier distribution. Besides these, the high level of defect incorporation in the multiple-quantum-well (MQW) active layer has often been discussed as a potential contributor to the green gap. Recent studies have revealed that the defect incorporation originated from two independent mechanisms: (i) inherent incorporation of impurities, such as carbon and oxygen, due to reduction in the growth temperature to grow the indium (In)-rich MQWs , and (ii) incorporation of the native defects formed at an n-type GaN surface [i.e., surface defects (SDs)] into the MQWs during the LT growth. Both mechanisms create nonradiative recombination centers (NRCs) in the MQW active layer, which act as a path for Shockley–Read–Hall (SRH) nonradiative recombination, thereby reducing IQE. , Recently, studies on the second of the above-mentioned mechanism are being actively conducted by several research groups as it is considered a key factor in the IQE improvement. Our recent studies showed that the SDs in an n-type GaN are most likely nitrogen vacancies (V N ), divacancies comprising Ga and N vacancies (V Ga V N ), and/or a V N impurity complex, which are intensively distributed within about 100 nm from the growth surface of n-type GaN. , Note that the SDs are easily incorporated with In atoms owing to strong affinity between them; therefore, an introduction of a GaInN or AlInN layer between the n-type GaN and the MQWs [i.e., an underlying layer (UL)] is very useful to improve the IQE by trapping the SDs therein. , However, a further increase in the In content and/or thickness of the UL to enhance the SD trapping frequently has negative impacts on the device performance because it generates threading dislocations (TDs) and absorbs the photons emitted from the MQWs. , This indicates that the introduction of a UL alone is insufficient to suppress the incorporation of SDs into the MQWs. As a method to further reduce the SDs in n-type GaN other than the introduction of a UL, we have demonstrated the MQWs grown on the surface-etched n-type GaN layer, which showed an improvement in the IQE by a factor of 2.5 in green LEDs .…”
Section: Introductionmentioning
confidence: 99%